ҚАЗАҚ ЖӘНЕ ТҮРІК ФОЛЬКЛОРЫНДАҒЫ ӨТІРІК ӨЛЕҢДЕР МЕН ӨТІРІК ӨЛЕҢДЕР АЙТЫСТАРЫ - Йылмаз, Мехмет Али (Journal of Oriental Studies, 2016)
Throughout the whole history, it was a dictionary in the society's who had been in love and they gave to each other various responsibility in the community or individuals in the irregulari-ties, injustices and their role in processing defects. By this direction the society had quite rich and humoris poems. By reading these poems we can see the traditions and customs, people's life style in poetry, thoughts, world view, the superstitious beliefs, working conditions, the troubles and frus-trations of Kazakh and Turkish society. So, poems may be on the base of individual or in the form of bickering. Usually,the poems in the form of two lovers who are bickering about one specific topic are exaggerated. However, a person (lover) does not have to answer always to the opponent who is in love.